Pushy Parisian Elbows: Taste for Comfort in Public Transport - Koning Martin; Haywood Luke (European Regional Science Association (ERSA), 2011)
Since they change the individuals' time perception, qualitative aspects of transport are increasingly discussed as factors influencing the choice between individualised and public transport. In this article we investigate, both analytically and empirically, the utility cost of congestion in public transport networks, the congestion being defined as the space available for travelers in trains. First, we propose a simple model integrating a qualitative component into the utility function of commuters. This enables us to underline the effect on the individual welfare, and modal decision, of reduced comfort in trains. For a policy aiming at reducing car usage, this "cross-modal externality" may significantly soften the overall modal switch. Therefore, it appears of major interest to appraise the utility cost of public transport congestion.. Using contingent methodology and survey data from central Paris subway - a relevant case study due to recent evolutions in transportation patterns- we then approximate this discomfort effect. According to answers of 533 line 1 users, this is equivalent to 5.7-8.1 minutes of excess travel, i.e. 29%-42% of average trip duration or 1.01-1.42 euro once translated in monetary terms. With the use of categorical estimates, we show that these figures significantly rise with trip time as well as levels of congestion, while being quite stable across individual characteristics. We conclude with policy implications by approximating the marginal benefit of subway decongestion at 0.25 euro/passenger*kilometer. This new parameter allows us to illustrate how considering comfort in public transport changes the picture when one comes to appraise evolutions in the Parisian transportation patterns. For example, decongestion benefits in undergrounds (3.5 M euros) due to a new tramway in South Paris overpass the time savings induced by this new infrastructure (2.7 M euros). Over 2000-2007, the increase in subway congestion costs may also be estimated at 100 M euros. Therefore, these figures underline the need for an accurate understanding of the perceived costs of travels.
Keywords: 330